Analisis Peran Komunikasi Interpersonal dalam Menangani Konflik Sosial di Kelas: Studi Kasus pada Mahasiswa Program Studi Komunikasi dan Penyiaran Islam Kelas 4A UIN Sultan Maulana Hasanuddin Banten - Destiyan Elviyana Nugraheni; Ahmad Faiq Al – Alawi; Adhi Kusuma (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Social conflict in the academic environments is a phenomenon that frequently occurs in student interactions. This research aims to analyze the role of interpersonal communication in handling social conflicts that occur in class 4A of the Islamic Communication and Broadcasting Study Program at UIN Sultan Maulana Hasanuddin Banten. The research method used is a qualitative approach with data collection techniques through observation, and in-depth interviews. The research subjects were 36 students from class 4A KPI. The results show that effective interpersonal communication plays an important role in resolving social conflicts through three main aspects namely communication openness that enables understanding of different perspectives, active listening skills that reduce misunderstandings, and empathy that builds bridges of understanding between individuals. Interpersonal communication strategies that have proven effective include open dialogue, communication mediation, and the formation of class discussion forums. This research concludes that structured and continuous interpersonal communication is able to transform destructive conflicts into constructive conflicts that encourage social and academic growth of students.